2013
DOI: 10.1186/1824-7288-39-22
|View full text |Cite
|
Sign up to set email alerts
|

Virological and clinical characterizations of respiratory infections in hospitalized children

Abstract: BackgroundThe purpose of this study was to determine the incidence and seasonal distribution of viral etiological agents and to compare their clinical manifestations and disease severity, including single and co infections.MethodsMultiplex reverse-transcription PCR was performed for the detection of viruses in nasopharyngeal aspirat. Disease severity was grouped using a categorization index as very mild/mild, and moderate/severe. Clinical and laboratory characteristics of hospitalized children with viral respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
92
9
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 37 publications
26
92
9
9
Order By: Relevance
“…This method has been used by others for the detection the hexon gene region of Adenovirus genome [7,14,15]. Similar findings have been reported by Helen Sarantis et al, who tested hexon gene (HVR-7) that was able to detect all serotypes of human adenoviruses known at that time with high sensitivity [17]. The statistical analysis revealed a significant difference between groups (X 2 = 11.064; P<0.01), where the viral DNA was detected in approximately a third (28.08%) of the total study groups (Table 3-1).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This method has been used by others for the detection the hexon gene region of Adenovirus genome [7,14,15]. Similar findings have been reported by Helen Sarantis et al, who tested hexon gene (HVR-7) that was able to detect all serotypes of human adenoviruses known at that time with high sensitivity [17]. The statistical analysis revealed a significant difference between groups (X 2 = 11.064; P<0.01), where the viral DNA was detected in approximately a third (28.08%) of the total study groups (Table 3-1).…”
Section: Resultssupporting
confidence: 74%
“…The statistical analysis revealed a significant difference between groups (X 2 = 11.064; P<0.01), where the viral DNA was detected in approximately a third (28.08%) of the total study groups (Table 3-1). The frequency of HAdVs positive cases in our study was higher for most studies than that reported in the Middle East such as Turkey 26.2% [17], Iran 14.4-22% [18][19][20], Israel 18.3% [21], Saudi Arabia 17.4% [22]. Other parts of the world reported different values like Kenya 14% [23], Korea 10.3% [24], Australia 7.3% [25], and Peru 6.2% [26].…”
Section: Resultscontrasting
confidence: 49%
“…In contrast with the findings of some previous studies [25][26][27], co-infections in the current study were not more severe than single infections [28][29][30]. In addition, consistent with our study, a study by Guo et al [31].…”
Section: Analysis Of Viral Infection and Crp Levelscontrasting
confidence: 57%
“…7,8 This variability could be due to normal oscillations of the virus circulation, with periodic, higher magnitude outbreaks; the world bibliography reflects divergences based on the region and years analyzed. 5,6 Although possible differences related to sample collection procedures (swab tests or, nasal or nasopharyngeal aspirate specimens) and the methodology used (traditional, real-time PCR) should be considered, local data regarding children hospitalized because of an ARI were obtained based on the detection of the viral genome by traditional PCR in nasopharyngeal aspirate specimens.…”
Section: Discussionmentioning
confidence: 99%